Hedonic and utilitarian shopping goals: a decade later. Issue 3 (3rd July 2018) - Bridges, Eileen
Abstract: I am pleased to be invited to share some thoughts about my article on the topic of hedonic and utilitarian shopping goals, which was co-authored by Renée Florsheim and published in the Journal of Business Research in 2008. Our article is among the most-cited ever to appear in the Journal of Business Research (JBR), which is quite an honor for us as authors as well as a strong statement about the importance of the topic. What I have done in this invited article is to begin by describing the process by which we developed our ideas, then briefly revisit our key findings, and discuss in some detail the directions that have been taken by later researchers citing our seminal work. Finally, I conclude with ideas on some of the factors that influence how a paper becomes widely cited and suggest areas of further research that could build upon this work.